2011
DOI: 10.1186/1479-5868-8-138
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a two-year school-based physical activity intervention among 7-9-year-old children

Abstract: BackgroundPhysical activity (PA) in children has declined in recent decades, highlighting the need for effective intervention programs for school-aged children. The main objective of this study was to assess to what extent PA during and after school hours changed among children who received a progressive two-year long intervention vs. that of children who only received general curriculum-based PA.MethodsA cluster randomized intervention study was conducted and six elementary schools randomly assigned to serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 34 publications
5
58
2
6
Order By: Relevance
“…Significant differences observed by sex for MVPA are consistent with other school‐based intervention programs where boys were demonstrated greater absolute increases in MVPA . This finding is counterintuitive because girls, especially older girls, often engage in lower MVPA than boys, thereby having relatively more room for improvement.…”
Section: Discussionsupporting
confidence: 82%
“…Significant differences observed by sex for MVPA are consistent with other school‐based intervention programs where boys were demonstrated greater absolute increases in MVPA . This finding is counterintuitive because girls, especially older girls, often engage in lower MVPA than boys, thereby having relatively more room for improvement.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Schuna et al 40 found that boys achieved greater MVPA levels than girls in the Keep It Moving (KIM) after-school programme. This difference between boys and girls has been reported elsewhere in the literature,45 46 though the reasons underlying this remain unclear. This finding suggests that there is a particular need to find ways to increase girls MVPA during extracurricular interventions.…”
Section: Discussionsupporting
confidence: 67%
“…Some previous studies have found a greater intervention effect on girls’ physical activity, 45,46 but others have found a greater effect on boys’ physical activity. 21,4749 In a meta-analysis of physical activity interventions in children, Metcalf et al 50 found no significant differences in intervention effects between sexes, but there was a trend toward girls responding more positively to the interventions than boys. Reviews of school-based obesity interventions suggest that boys and girls may respond differently to interventions, 51,52 with girls potentially favoring educational interventions and boys responding better to environmental interventions.…”
Section: Discussionmentioning
confidence: 99%